Transformasi Supervisi Pendidikan Madrasah: Menuju Pendidikan Islam yang Berkualitas dan Berdaya Saing - Muhammad Bahrudin; Fegy Diah Yasminar (Milenial: Journal for Teachers and Learning, 2025)
Madrasah education supervision is a coaching process that aims to improve the quality of learning and teacher professionalism through supervision that is constructive, democratic, and oriented towards continuous improvement. This article comprehensively discusses the meaning of supervision, the factors that influence its implementation, the aims and functions of supervision in madrasas, the types of supervision, the processes followed, as well as the techniques, approaches and methods used. The results of the study show that supervision of madrasa education not only functions as a monitoring tool, but also as a strategic effort to integrate religious and general curricula, increase teacher competence, create a collaborative work climate, and strengthen institutional governance. Effective supervision requires the involvement of madrasa heads, teachers and supervisors in carrying out their respective roles with the principles of cooperation and continuous development. With Thus, supervision of madrasa education can be used as a means of realizing quality education that is in line with Islamic values ​​while also responding to the challenges of modern education